Case for diagnosis - Han Ma; Huaiqiu Huang; Meirong Li; Wei Lai; Chun Lu (Sociedade Brasileira de Dermatologia, 2014)
Cutaneous Rosai-Dorfman disease is a rare, lymphoproliferative disease. It is benign and self-limited, only involves skin and subcutaneous tissue and typically occurs as histiocyte-rich inflammatory infiltrates, manifesting as erythematous to brown papules, plaques, or nodules, without predilection for site. The authors describe a case of cutaneous Rosai-Dorfman disease in a 72-year-old man who presented erythematous and scaled plaque on the right neck for three months without systemic symptoms. Owing to local involvement, the patient received a surgery to exsect the lesion completely and remained asymptomatic with no signs of recurrence at the 9-month follow up.